Efficiency of various blade types in rowing - Kleshnev, V. (Sports Biomechanics, 2026)
The purposes of the study were: a) to develop a novel method to determine the centre of pressure acting on the blade by combining measurements from multiple shaft-mounted strain-gauge sensors, b) to experimentally evaluate the factors affecting blade efficiency and overall effectiveness in rowing using three different blade designs. One international-level male rower performed step-rate trials using each blade type, while biomechanical data were collected with the BioRow system. Results showed that although biomechanical characteristics such as stroke length, force profiles, and power output were generally similar across blades, hydrodynamic performance differed. Fat2 blades, due to their larger surface area, demonstrated the lowest blade slippage and highest propulsive efficiency. However, Comp blades - despite having the smallest area - provided the most effective performance, defined as the highest boat speed per unit of rower power, as reflected by the lowest Gross Drag Factor. Analysis of forces revealed that the actual centre of pressure was located more inboard than previously assumed, resulting in 7-8% heavier true gearing ratios. These findings suggest that blade effectiveness cannot be predicted solely from its slippage through the water and that smaller Comp blades may reduce rotational and axial losses, contributing to improved rowing performance.